Tierethik als Gestaltung: vom Ereignis zur beziehungsorientierten Verantwortungsübernahme - Schütz, Nils (Theologische Bibliothek Töpelmann, 2025)
Social relations between humans and animals are complex and require nuanced ethical consideration. This volume investigates human-animal relations from a constructive-critical, and theological perspective